Stress distribution of different implant connections associated with multiple implant-supported prostheses - Goiato, Marcelo Coelho [UNESP] (2018)
In some clinical situations, the clinician may encounter previously installed implants that should be associated with other implants for a proper rehabilitation. The aim of this study was to evaluate the biomechanical behaviour of a multiple prosthesis joined by different implant connections using photoelasticity. Photoelastic models with a screwed fixed prosthesis supported by implants with different connection systems (Morse taper, external hexagon, internal hexagon, and Flexcone), and different combinations among them, were fabricated. Each assembly was placed in a circular polariscope, and axial and oblique (45°) loads of 100 N were applied on the occlusal surface of the crowns. The fringe patterns were photographed and the analysis was performed by counting the number of high-intensity fringes and also according to the stress distribution region where they appeared. Among implants of the same connection, the external connections obtained a greater number of high intensity fringes when compared to the internal connections. From the biomechanical point of view, the association between different types of connections obtained positive results.